2014
DOI: 10.4102/ajlm.v3i2.200
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality in national reference laboratories: The role of SLMTA and mentorship

Abstract: BackgroundThe Nigerian Institute of Medical Research houses two reference laboratories: the virology and tuberculosis laboratories. Both were enrolled in the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme.ObjectiveTo describe the impact of SLMTA and discuss factors affecting the results, with an emphasis on mentorship.MethodsThe SLMTA programme was implemented from April 2010 through November 2012. Participants attended three workshops and executed quality improvement projects; labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Other studies have also noted that supplementing SLMTA with additional training and mentoring may be beneficial. 9,10,11 Our findings, when joined with these others, suggest that combining SLMTA with other strategies in a QMS programme may lead to synergistic improvement.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Other studies have also noted that supplementing SLMTA with additional training and mentoring may be beneficial. 9,10,11 Our findings, when joined with these others, suggest that combining SLMTA with other strategies in a QMS programme may lead to synergistic improvement.…”
Section: Discussionsupporting
confidence: 60%
“…9 This checklist yields qualitative results rather than a numerical score and highlights areas of focus for accreditation preparation.…”
Section: Research Methods and Designmentioning
confidence: 99%
“…9 SLMTA mentorship approaches have ranged from standard short-term visits 10,11 to newer models of peer or embedded mentoring. 11,12 In the standard short-term model, a mentor visits the mentee laboratory and stays in the laboratory for a short stint, often a week or less. During this period, the laboratory quality officer works under the guidance of the mentor to address laboratory quality gaps identified during prior assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Our LQSI approach using a full-time staff of embedded quality improvement mentors has proven highly effective in implementing a quality management system in a large number of hospital laboratories in a relatively short period. Others have demonstrated that mentorship assists laboratories to implement quality improvement activities 23 , 24 , 31 . However, we have shown how the regular presence of fully dedicated mentors and a detailed quality management system action plan in the local language improves the rate of quality management system implementation.…”
Section: Discussionmentioning
confidence: 62%